Physical and non-physical factors affecting rental rate for shop unit within shopping centre [electronic resource] : some evidence from Johor Bahru City Centre - Sim, Sui Chen, 1986-; Fakulti Kejuruteraan dan Sains Geoinformasi (2010)
Project Paper (Sarjana Muda Sains (Pengurusan Harta Tanah)) - Universiti Teknologi Malaysia, 2010